2002
DOI: 10.1093/glycob/cwf070
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-related expression of  1,2fucosylated antigens on colorectal carcinoma cells and its suppression by cell-mediated priming using sugar acceptors for  1,2fucosyltransferase

Abstract: The accumulation of alpha1,2fucosylated antigens, such as Y (Fucalpha1,2Galbeta1,4 [Fucalpha1,3]GlcNAcbeta), Le(b) (Fucalpha1,2Galbeta1,3-[Fucalpha1,4]GlcNAcbeta), and H type 2 (Fucalpha1,2 Galbeta1,4GlcNAcbeta) occurs specifically within human colorectal tumor tissues and can be detected by an antifucosylated antigen antibody, such as the YB-2 antibody. In the present investigation, we found that the expression of these antigens bearing an alpha1,2-linked fucose correlated with the resistance of the tumor cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…34 Other studies showed that blocking a(1,2)-fucosylation increased cell sensitivity to anticancer drugs. 43 Interestingly, we have previously shown that FUT1 affected E-selectin-mediated adhesion in some cell lines, including HepG2 cells (see also the present study) and the colon carcinoma cells HT29, but had no effect on other cells, such as pancreatic cancer cells BxPC3, 11 suggesting that the effect of FUT1 is cell-dependent.…”
Section: Discussionsupporting
confidence: 53%
“…34 Other studies showed that blocking a(1,2)-fucosylation increased cell sensitivity to anticancer drugs. 43 Interestingly, we have previously shown that FUT1 affected E-selectin-mediated adhesion in some cell lines, including HepG2 cells (see also the present study) and the colon carcinoma cells HT29, but had no effect on other cells, such as pancreatic cancer cells BxPC3, 11 suggesting that the effect of FUT1 is cell-dependent.…”
Section: Discussionsupporting
confidence: 53%
“…In contrast, cell-mediated priming by certain glycoconjugates in colorectal cancer cells showed that novel antitumor agents might exist among such glycoconjugates [5]. However, it is plausible that treatment of cancer cells with the present sugar-cholestanols achieves more potent advantages as an anticancer agent.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the amounts of tumor-associated antigens including α1-2fucosylated antigens and the SLX antigen expressed on the cancer cell surface, could be selectively suppressed, and this enhanced the susceptibility of cancer cells to anticancer treatments [5]. More recently, the same primers were shown to have strong inhibiting actions on the proliferation of cancer cells when the concentrations of the primers were increased [17,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations